1974
DOI: 10.1139/v74-306
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Stereochemistry of (±)-(4a,13b-trans)-2,3,4,4a,8,9,13b,14-Octahydro-1H-benzo[6,7]cyclohepta[1,2,3-de]pyrido[2,1-a]-isoquinoline Hydrochloride (Taclamine Hydrochloride), a Novel Psychotropic Agent

Abstract: in experimental animals. Preliminary pharmacological res~llts have been described (1)and a fill1 paper is in preparation. In this report we describe the synthesis a n d stereochemistry of taclamine hydrochloride.T h e synthesis of taclamine.HC1 1 has been accomplislied through two independent pathways (see Scheme I). In the first, 10,1 I-dihydro-(2) (2) was condensed with 8-valerolactone t o give the hydroxyamide 3, which o n treatment with p h o s p h o r o~~s oxychloride undergoes a double cyclization to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…The 4a,13b relative configuration of the dechloro amino ketones related to 24-27 and to 28-32 has been confirmed indirectly by crystallographic studies,23 and it had been noted28 that the NMR signal of the C13b hydrogen of the 4a,13b-trans isomer appears as a triplet while that of the 4a,13b-cis isomer is a doublet. Similar splitting patterns for the C13b hydrogens of the amino ketones [24][25][26][27][28][29][30][31][32] (see Table I) lend support to the configurational assignments shown in Scheme II and Table I.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The 4a,13b relative configuration of the dechloro amino ketones related to 24-27 and to 28-32 has been confirmed indirectly by crystallographic studies,23 and it had been noted28 that the NMR signal of the C13b hydrogen of the 4a,13b-trans isomer appears as a triplet while that of the 4a,13b-cis isomer is a doublet. Similar splitting patterns for the C13b hydrogens of the amino ketones [24][25][26][27][28][29][30][31][32] (see Table I) lend support to the configurational assignments shown in Scheme II and Table I.…”
supporting
confidence: 61%
“…The Schiff bases were reacted, as their hydrochloride salts, with methyl vinyl ketone to afford the pentacyclic amino ketones shown in Scheme II and Table I. The 6-, 9-, 10-, and 11-chloro Schiff bases 19-23 gave mixtures of the cis (24)(25)(26)(27) and trans (28)(29)(30)(31) amino ketones with a preponderance of the trans isomers being formed. No cis isomer could be isolated on reaction of the 4-chloro Schiff base 23 with methyl vinyl ketone.…”
mentioning
confidence: 99%
“…Various chemical and pharmacological studies have been undertaken in recent years at the AYERST Research Laboratories of Canada, in order to determine the topography of the central dopamine receptor and its mode of interaction with neuroleptic agents of the benzocycloheptapyridoisoquinoline series. Some of these studies have been reported by Bruderlein, Humber & Pelz (1974) on synthetic procedures; Humber, Bruderlein & Voith (1975) on the mode of interaction; Humber, Bruderlein, Philipp, G6tz & Voith (1979) on the effect of modifications to ring E of the neuroleptic butaclamol (Ia); and on the effect of modifications to the regions occupied by the A and B rings of (Ia). Besides the chemical synthesis and pharmacological evaluation of the compounds, the studies include stereochemical * NRCC Publication No.…”
Section: Introductionmentioning
confidence: 99%
“…Percent inhibition was calculated with the formula, % = 100(1 -a/b), where a is the sum or the reaction diameters in the treated animals and b the sum of the reaction diameters in the control animals.21 Each variable was tested in groups of five rats. 3b,4,5,7,8b,9,6-cT dipyrazole (1). A mixture of 1.11 g (5 mmol) of 4,11 1 mL (ca.…”
mentioning
confidence: 99%
“…Anal. (C14H18N4) C, , 4,5,8b,9,dipyrazole (6). This compound was prepared in 26% yield by a similar procedure as for 1 and 5.…”
mentioning
confidence: 99%